An Overview of the Knowledge and Motivation of IMCI Staff Regarding the Implementation of IMCI at the Lubuk Buaya Public Health Center, Padang - Siregar, Nurhayati; Sukmawati, Yofa; Yuliarni, Eza (Basic and Applied Nursing Research Journal, 2021)
Introduction: Indonesia is one of the developing countries with a high under-five mortality rate due to the rough handling of Integrated Management of Childhood Illness (IMCI). Diseases that cause death can generally be treated at the hospital level, but it is still difficult at the public health center level. Public Health Centers have implemented (IMCI). Suppose they meet the criteria for implementing/implementing the IMCI approach at least 60% of the number of visits by sick toddlers. This study aimed to describe the knowledge and motivation of IMCI implementers regarding the implementation of IMCI at Lubuk Buaya Public Health Center, Padang, in 2014. Method: This research is descriptive. This research was conducted at the Lubuk Buaya Health Center Padang in May 2014. The population in this study were all IMCI implementers who were actively working at the Lubuk Buaya Public Health Center, Padang, with 37 people. Sampling with total sampling technique and analyzed univariately. Results: From 37 staff implementing IMCI, it was found that 31 (83.8%) staff had implemented IMCI well, 36 (97.3%) staff had high knowledge, and 23 (62.2%) staff had high motivation. Conclusions: This study shows that the knowledge and motivation of IMCI implementers are good in implementing IMCI. It is hoped that every IMCI implementer will further increase knowledge about IMCI and its performance so that all sick toddlers get the best IMCI services to prevent death in these toddlers.